Management styles of the top and middle managers : Tengku Ampuan Afzan Teacher Training Collelge, Kuantan - Suriati Abdullah (Kulliyyah of Islamic Revealed Knowledge and Human SciencesInternational Islamic University Malaysia, 1998)
This study investigates the different managerial stylles adopted and practised by the top and middle managers in Tengku Ampuan Afzan Teacher Training College (TAATTC), Kuantan. It also examines the compatability between the managers' styles and the situation. A questionnaire was utilised as a means of gathering data. The Leader Effectiveness and Adaptability Description - Perception of Self (LEAD-SELF) questionnaire was complete by the managers, while the Leader Effectiveness and Adaptability Description-Perception of Other (LEAD-OTHER) questionnaire was completed by the lecturers. Both LEAD instruments measure four leadership styles and style flexibility. The population under consideration was made up of two top managers, five middles managers and one hundred lecturers from Tengku Ampuan Afzan Teacher Training College in Kuantan. All questionnaires distributed were returned, representing a return rate of 100 per cent. Raw scores were used to analyse data from the LEAD-SELF instrument. Mean scores from leadership style profile and leadership style adaptibility were computed for data from the LEAD-OTHER instrument. The results suggest that thetop and middle managers in TAATTC are mainly of the "selling" type, with low leaddership style adaptability. In addition, they also suggest that there is a need to shift leadership styles to a more participating and delegating nature, whereby the managers and subordinates share in decision-making. Subordinates should also be responsible for directing their own behaviour. This study ends with recommendations for the adoption of appointment and promotion policies based on the administrator's ability to lead effectively, in addition to seniority, as well as, other criteria,. The need for in-service educational training on modern managemebnt developments is another recommendation to further improve and managerial skills, which in turn, will facilitate flexibility of styles.